The handbook of communication and corporate social responsibility - Ihlen, Oyvind; Bartlett, Jennifer L.; May, Steve (Steve Kent) 1961- (Chichester, West Sussex, [England] John Wiley & Sons, Ltd., 2014)
"This book represents the definitive research collection for corporate social responsibility communication, offering cross-disciplinary and international perspectives from the top scholars in the field. Addresses a gap in the existing CSR literature Demonstrates the relevance of effective CSR communication for the management of organizations The 28 contributions come from top scholars in public relations, organizational communication, reputation management, marketing and management"--Provided by publisher.
"While there is a huge amount of literature on corporate social responsibility (CSR), there is relatively little advice to be found regarding how CSR should be communicated.This book represents the definitive research collection for CSR communication, taking stock of the existing recommendations and demonstrating how the communication disciplines can make contributions to central research gaps in the CSR literature. Contributions from leading scholars in public relations, organizational communication, reputation management, marketing and management show how theories of discourse, internal communication, cognitive psychology, reputation and rhetoric enrich our understanding of CSR communication and how this influences the way organizations should be managed"--Provided by publisher.
PART 1:INTRODUCTION.-- 1.Corporate Social Responsibility and Communication (Øyvind Ihlen, Jennifer L. Bartlett, & Steve May).-- 2.The Paradoxes of Communicating Corporate Social Responsibility (Sandra Waddock & Bradley K. Googins).-- PART 2:FIELD OVERVIEWS.-- 3.Management, Communication and Corporate Social Responsibility (Jennifer L. Bartlett & Bree Devin).-- 4.Public Relations and Corporate Social Responsibility (Jennifer L. Bartlett).-- 5.Organizational Communication and Corporate Social Responsibility (Steve May).-- 6.Marketing and Corporate Social Responsibility (Peggy Simcic Brønn).-- 7.Reputation Management and Corporate Social Responsibility (Mark Eisenegger & Mario Schranz).-- 8.Rhetoric and Corporate Social Responsibility (Øyvind Ihlen).-- PART 3:CORPORATE SOCIAL RESPONSIBILITY COMMUNICATION IN ACTION. -- Concepts and Aspects. -- 9. Ethics: CSR, Power and Strategic Communication (Jairo Lugo-Ocando, Jacquie L'Etang & Zeti Ahmad). -- 10. Risk Communication and Corporate Social Responsibility: The Essence of Sound Management for Risk Bearers, Generators and Arbiters (Michael J. Palenchar, Tatjana M. Hocke, & Robert L. Heath). -- 11.Trust and Credibility as Basis of Corporate Social Responsibility: (Mass-) Mediated Construction of Responsibility and Accountability (Günter Bentele & Howard Nothhaft). -- 12.Corporate Social Responsibility Communication and Dialogue (Urša Golob & Klement Podnar). -- 13.Transparency and Neo-liberal Logics of Corporate Economic and Social Responsibility (Majia H. Nadesan). -- 14.The Concept of Stakeholders and its Relevance for CSR Communication (Juliana Raupp). -- 15.Significance of Sector-Specific Corporate Social Responsibility Initiatives: Status and Role in Different Sectors (Angela Mak, Augustine Pang, & Joanne Lee). -- Tools and Processes. -- 16.Corporate (Social) Responsibility and Issues Management: Motive and Rationale for Issue Discourse and Organizational Change (Robert L. Heath & Michael J. Palenchar). -- 17.Communicating Corporate Social Responsibility through Nonfinancial Reports (Cynthia Clark Williams & Elise Perrault Crawford). -- 18.Communicating Corporate Social Responsibility through the Internet and Social Media (Paul Capriotti). -- 19.Communicating Corporate Social Responsibility through Corporate Image Advertising (Alan A. Pomering). -- 20.New Partnerships for a New Generation of Corporate Social Responsibility (Melissa J. Bator & Cynthia Stohl). -- 21.Media Relations and Corporate Social Responsibility (Craig C. Carroll). -- 22.NGOs as Communicative Actors within Corporate Social Responsibility Efforts (Sarah E. Dempsey). -- 23.Communication and Corporate Social Responsibility: A Storytelling Perspective (Stefan Wehmeier & Friederike Schultz). -- PART 4:COMMENTARIES AND CONCLUSIONS. -- 24.Interrogating the Communicative Dimensions of Corporate Social Responsibility (Lars Thøger Christensen & George Cheney). -- 25.A Provocation: Thinking the 'Social' into Corporate Social Responsibility (Judy Motion & Shirley Leitch). -- 26.Commentary: The View from Management (Güler Aras & David Crowther). -- 27.The View from Organizational Studies: A Discourse Based Understanding of CSR and Communication (David Grant & Daniel Nyberg).
Includes bibliographical references and indexes.
Keywords: Social responsibility of business; Mass media and business; Business communication